Error analysis of inflectional morphemes in the descriptive essay of senior English learners at Panjshir institute of higher education - Kamran Hatifi; Sayed Zahir Nazimi; Assadullah Qatey (Science and Education, 2024)
This study aims to identify, describe, and analyze errors assigned in the area of inflectional morphemes by the 4th-year EFL students at the Panjshir Higher Education Institute Department of English Faculty of Education during the academic year 2023. To identify the areas of problems and find out what makes these areas difficult, errors are classified concerning the eight types of inflectional morphemes. The mechanism of applying this version of error analysis on the data gathered passes through different analytical levels, starting with data collection, identification of the point of difficulty, description, explanation, and ending with the evaluation of errors. The current study was conducted to find out students’ errors in using inflectional morphemes that include: past tense inflection “ed1”, plural inflection “s”, present inflection “ing”, third person singular “s”, past participle “ed2”, possessive inflection “‘s”, comparative “er” and superlative inflection “est”. This study aims to find out the errors made by learners in using inflectional morphemes, and most importantly, the sort of such errors; whether they are, errors of omission, addition, misinformation, or misordering. The subjects of this study were 35 EFL students in their fourth -year at the Panjshir Higher Education Institute. The results of the analysis reveal that the total number of errors found in the students’ essays is 183. The objective outcome of the analysis conducted displays several findings and conclusions; among these are, the percentage of “ed1” morpheme errors comprised 32.24% of the total types of errors, the second rank is the plural morpheme “s” errors =26.22%, the ‘ing” morpheme errors= 12.56%, the third person singular “s” =8%,”ed2” errors=7%, possessive morpheme errors =6.5%, Finally the comparative “er”4 errors and the superlative “est” comprised the lowest rank of percentage; that is 2.7%. Based on the findings of this research, it is hoped that it would help other researchers to build up further discussions and research on errors with broader aspects and different subjects.